High-throughput DNA sequencing of environmentally insulted latent fingerprints after visualization with nanoscale columnar-thin-film technique. Issue 5 (September 2021) - Tiedge, Teresa M.; Nagachar, Nivedita; Wendt, Frank R.; Lakhtakia, Akhlesh; Roy, Reena
Highlights: Human identity using SNPs is achieved from environmentally insulted fingerprints. 802 fingerprints on forensically relevant substrates exposed to various insults. DNA from these samples were analyzed with and without CTF enhancement. CTF enhancement with several evaporants showed no inhibition of DNA sequencing. The Precision ID Identity Panel performs well on CTF and non-CTF samples. Abstract: The goals of this study were to (a) ascertain human identity capabilities of DNA obtained from latent fingerprints that have been first environmentally insulted and then developed by the deposition of a columnar thin film (CTF), and (b) to determine if the CTF process and material are detrimental to single nucleotide polymorphism (SNP) analysis. Fingerprints were deposited on five different types of substrates and aged for one day, 7 days or 30 days while being environmentally insulted under one of the four conditions: 16.6 °C and 60% relative humidity (RH) (Condition A), 24.5 °C and 60% RH (Condition B), 35 °C and 67% RH (Condition C) and a cold condition (Condition D). Then CTF technique was then on 59% of these fingerprints. DNA samples from 805 fingerprints were extracted, quantified, subjected to manual library preparation using the Precision ID Identity Panel, and underwent high-throughput sequencing. The Ion S5™ platform was employed to sequence 124 SNP amplicons. SNPs were successfully sequenced from 802/805 samples. Total read depth was consistent across environmental conditions, and majority of samples had 100% profile completeness and 100% concordance. Anecdotally, libraries that were amplified with a higher cycle number had more 'Major Allele Frequency' flags compared to samples amplified with 23 cycle numbers, possibly due to stochastic effects. Neither the substrates nor the CTF process and materials inhibit downstream DNA analysis. DNA of low quality and quantity from the chosen samples can be sequenced using the Precision ID Identity Panel on the Ion S5™ platform which performed well, however, a different approach may be needed if spurious alleles are suspected.